Thomas Sowell. Migrations and cultures : a world view. Nueva York : Basic Books, A Division of Harper Collins Publishers, 1996 - Giorguli Saucedo, Silvia Elena (Estudios Demográficos y Urbanos, 2001)
Thomas Sowell, Migrations and Cultures. A World View, Nueva York, Basic Books, A Division of Harper Collins Publishers, 1996.